The diversity of recreational knowledge in Sulalatus Salatin: reflection of intellectuality of Melaka sultanate - Jasni, Khairul Zainie; Noor Muhammad, Salmah Jan (Human Resource Management Academic Research Society, 2018)
The culture and the arts of the palace during the Malay sultanate of Melaka were very exclusive compared to the common people. The rulers of the kingdom must demonstrate the strength and greatness of all things in order to qualify themselves as rulers of the kingdom. Great rulers would then be able to expand its influence in the surrounding area. Therefore, the objective of this study is to identify and discuss the recreational knowledge in Sulalatus Salatin as a reflection of the intellect of the Malay rulers of Melaka. The method used is a text analysis to obtain the data of study. The result of the discussion found that there were various recreational practices conducted by the Melaka Malay rulers in the texts. The type of recreation performed is relaxed and rugged between are amongst that discussed in this article to demonstrate the power of the king in various skills besides highlighting the integrity of the government. The results of this study are also expected to benefit the community to know the leisure activities carried out by Melaka Malay rulers in the text of Sulalatus Salatin.